2012
DOI: 10.1159/000339493
|View full text |Cite
|
Sign up to set email alerts
|

Bimonthly Regimen of High-Dose Leucovorin, Infusional 5-Fluorouracil, Epirubicin and Cisplatin (Modified ECF) as Adjuvant Chemotherapy in Resected Gastric Adenocarcinoma

Abstract: <b><i>Background:</i></b> The administration of the de Gramont regimen in combination with cisplatin and epirubicin (modified ECF) has previously been reported as a treatment for advanced gastric cancer, but here we report this regimen combination in an adjuvant setting for the first time. <b><i>Methods:</i></b> Forty-eight patients with curatively resected gastric cancer were treated. Each 2-week cycle consisted of epirubicin (50 mg/m<sup>2</sup>), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Comparative and noncomparative clinical trials have demonstrated that regimens containing conventional doses of epirubicin achieved equivalent even higher objective response rates and overall median survival as similar doxorubicin-containing regimens in the treatment of advanced and early breast cancer, non-small cell lung cancer (NSCLC), small cell lung cancer (SCLC), nonHodgkin's lymphoma, ovarian cancer, gastric cancer and nonresectable primary hepatocellular carcinoma (Nair et al, 1998;Khasraw et al, 2012). Recently, dose-intensive regimens of epirubicin have achieved high response rates in a number of malignancies including early and advanced breast cancer and lung cancer (Unek et al, 2012;Vici et al, 2012). However, improved overall survival has not yet been demonstrated.…”
Section: Schedule-dependent Effects Of Kappa-selenocarrageenan In Commentioning
confidence: 99%
“…Comparative and noncomparative clinical trials have demonstrated that regimens containing conventional doses of epirubicin achieved equivalent even higher objective response rates and overall median survival as similar doxorubicin-containing regimens in the treatment of advanced and early breast cancer, non-small cell lung cancer (NSCLC), small cell lung cancer (SCLC), nonHodgkin's lymphoma, ovarian cancer, gastric cancer and nonresectable primary hepatocellular carcinoma (Nair et al, 1998;Khasraw et al, 2012). Recently, dose-intensive regimens of epirubicin have achieved high response rates in a number of malignancies including early and advanced breast cancer and lung cancer (Unek et al, 2012;Vici et al, 2012). However, improved overall survival has not yet been demonstrated.…”
Section: Schedule-dependent Effects Of Kappa-selenocarrageenan In Commentioning
confidence: 99%